EVALUATION OF PROGNOSTIC FACTORS IN PATIENTS WITH RELAPSED HODGKIN’S LYMPHOMA UNDERGOING AUTOLOGOUS STEM CELL TRANSPLANT: Relapsed Hodgkin’s Lymphoma - Iftikhar, Jhanzeb; Sarwar, Hafiz Abubakar; Sheikh, Fareeha; Shah, Mohammad Iqbal; Khan, Shafqual Ali; Bakar, Muhammad Abu; Siddiqui, Neelam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify the prognostic factors in relapsed Hodgkin’s Lymphoma patients with regards to their impact on the outcome of autologous hematopoietic stem cell transplant. Study Design: Retrospective observational study. Place and Duration of Study: Department of Medical Oncology, Shaukat Khanum Memorial Cancer Hospital & Research Center, Lahore, Jun 1999 to Jun 2019. Methodology: Out of a total of 2061 Hodgkin’s Lymphoma patients, 37 (1.8%) patients with relapsed disease underwent autotransplant and were studied using the Hospital Information System. We obtained details of clinicopathological factors, treatment, and outcome. In our study, the outcome variable was event after transplant (relapse/disease progression/death). Results: Among the 37 relapsed Hodgkin’s Lymphoma patients undergoing auto-transplant, 24 (64.9%) patients had an early relapse after first-line chemotherapy. In this early relapse group of 24 patients, 9 (37.5%) remained well after auto-transplant but 15 (62.5%) patients had an event. Out of 37 relapsed Hodgkin’s Lymphoma patients undergoing auto-transplant, a complete response on pre-transplant imaging was observed in 24 (64.9%) patients. In those 24 patients with a complete response on pre-transplant imaging, 16 (66.7%) patients remained well after transplant while 8 (33.3%) patients had a worse event. Twoyear progression-free and overall survival proportions were 56% and 77% respectively. Conclusion: Complete metabolic response on pre-transplant imaging was associated with better overall survival. Adverse factors observed were initial short duration of complete response, bulky disease at relapse, variables comprising international prognostic score, B symptoms, and raised erythrocyte sedimentation rate at relapse.